Developing an Excel-Based Education Management System for Engineering Programs - YASIN, HAMZA (İstanbul Kültür Üniversitesi, 2025)
In modern engineering education, aligning curricula with international accreditation standards (e.g., ABET, MÜDEK) requires systematic program planning, outcome assessment, and continuous improvement. However, manual processes for mapping Program Outcomes (POs) to Course Outcomes (COs) and collecting assessment data impose significant faculty burdens, often compromising consistency and traceability. This thesis proposes an automated framework to streamline accreditation processes through structured PO-CO alignment and data-driven assessment. The framework consists of three phases: (1) program planning, strategically distributing POs across the curriculum; (2) course and assessment planning, designing CO-focused evaluations; and (3) detailed assessment design, ensuring alignment with program-level expectations. An Excel-VBA tool was developed to operationalize the framework, featuring dynamic CO-PO mapping, deviation analysis, and automated reporting. This enables real-time curriculum monitoring and corrective actions while enhancing faculty collaboration. A case study at Istanbul Kültür University demonstrated the framework's effectiveness, showing improved assessment accuracy, reduced faculty workload, and better curriculum management. The study presents a practical, unified approach to program assessment, supporting accreditation compliance while fostering continuous improvement in engineering education. The framework offers a replicable model for institutions committed to outcome-based education and sustainable accreditation practices. Future work may explore integration with learning management systems, machine learning for predictive analysis, multidisciplinary applications, and optimization techniques for data-driven decision-making.
Keywords: Program Outcomes; Course Outcomes; Outcome-Based Education; Accreditation; Assessment Planning; Excel-VBA